Energy Compensation Following a Supervised Exercise Intervention in Women Living With Overweight/Obesity Is Accompanied by an Early and Sustained Decrease in Non-structured Physical Activity - Riou, Marie-Ève; Jomphe-Tremblay, Simon; Lamothe, Gilles; Finlayson, Graham Stuart; Blundell, John Edward; Décarie-Spain, Léa; Gagnon, Jean-Christian; Doucet, Éric (Frontiers in Physiology, 2019)
Background/Objectives: Body composition (BC) does not always vary as a function of exercise induced energy expenditure (exercise EE - resting EE). Energy balance variables were measured to understand energy compensation (EC) in response to an exercise intervention performed at low (LOW) or moderate (MOD) intensity. Subjects/Methods: Twenty-one women with overweight/obesity (33±5 kg/m²; 29±10 yrs; 31±4 ml O2/kg/min) were randomised to a 3-month LOW or MOD (40 or 60% of , respectively) matched to expend 1500 kcal/week (compliance=97±5%). Body energy stores (DXA), energy intake (EI) (food menu and food diaries), resting EE (indirect calorimetry), total EE (doubly-labelled water), time spent in different activities (accelerometers), appetite (visual analogue scale), eating behaviour traits and food reward (liking and wanting) were assessed at baseline, after weeks 1 and 2 and at the end of the 3-month exercise intervention. Results: EC based on BC changes (fat mass and fat-free mass) was 49±79% and 161±88% in LOW and MOD groups, respectively (p=0.010). EI did not change significantly during the intervention. However, eating behaviour traits and food reward had changed by the end of the 3-month supervised exercise. Non-structured physical activity (NSPA) decreased across the intervention (p<0.002), independent of the intensity of the exercise training. Conclusion: Women with overweight/obesity training at LOW presented lower EC for a given energy cost of exercise. Our results strongly suggest that NSPA plays a major role in mediating the effects of exercise on energy balance and ultimately on changes in BC.